2018
DOI: 10.1016/j.jml.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Context, facial expression and prosody in irony processing

Abstract: While incongruence with the background context is a powerful cue for irony, in spoken conversation ironic utterances often bear non-contextual cues, such as marked tone of voice and/or facial expression. In Experiment 1, we show that ironic prosody and facial expression can be correctly discriminated as such in a categorization task, even though the boundaries between ironic and non-ironic cues are somewhat fuzzy. However, an act-out task (Experiments 2 & 3) reveals that prosody and facial expression are consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
52
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 50 publications
7
52
1
Order By: Relevance
“…The absence of consensus amongst these studies could be explained by the use of different kinds of task (e.g., rating of prosodic cues in Woodland and Voyer (2011), discrimination task in Voyer et al (2014) and Deliens et al (2017), interpretation task in Deliens et al (2018) and Peters et al, (2015) with the presence or not of time limit to answer in these studies) and by the presence of individual differences regarding how people use prosody when understanding utterances. Bishop and colleagues (Bishop, 2012;Jun and Bishop, 2015) suggested that the use of prosodic information for sentence interpretation may differ across English-speaking listeners.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…The absence of consensus amongst these studies could be explained by the use of different kinds of task (e.g., rating of prosodic cues in Woodland and Voyer (2011), discrimination task in Voyer et al (2014) and Deliens et al (2017), interpretation task in Deliens et al (2018) and Peters et al, (2015) with the presence or not of time limit to answer in these studies) and by the presence of individual differences regarding how people use prosody when understanding utterances. Bishop and colleagues (Bishop, 2012;Jun and Bishop, 2015) suggested that the use of prosodic information for sentence interpretation may differ across English-speaking listeners.…”
Section: Introductionmentioning
confidence: 98%
“…While the impact of contextual incongruity or prosody on understanding irony has led to a significant amount of research, the influence of the interplay between these markers on irony and sarcasm understanding have only recently been investigated in English (Woodland and Voyer, 2011;Voyer et al, 2014;Peters et al, 2015) and in French (Deliens et al, 2017;Deliens et al, 2018). Developing different experiments in English, Voyer et al (2014) found a strong interaction between context and prosody, concluding that prosody contributes to emphasizing the contrast effect in sarcasm perception.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, a few studies have applied online measures, such as eye‐tracking and event‐related brain potentials (ERPs), to investigate how readers keep track of temporal and emotional shifts in stories, and have demonstrated that readers are sensitive to mismatches between a character's expected and described emotional states [Carminati & Knoeferle, 2013, 2016; Komeda & Kusumi, 2006; Leuthold, Filik, Murphy, & Mackenzie, 2012; Munster, Carminati, & Knoeferle, 2014; Ralph‐Nearman & Filik, 2018; Rinck & Bower, 2000; Vega, 1996; Zwaan, 1996]. Moreover, some researchers have examined the online processes underlying sarcasm comprehension using eye‐tracking [e.g., Au‐Yeung, Kaakinen, Liversedge, & Benson, 2015; Deliens, Antoniou, Clin, Ostashchenko, & Kissine, 2018; Filik, Howman, Ralph‐Nearman, & Giora, 2018; Filik, Leuthold, Wallington, & Page, 2014; Filik & Moxey, 2010; Kaakinen, Olkoniemi, Kinnari, & Hyönä, 2014; Olkoniemi, Ranta, & Kaakinen, 2016; Olkoniemi, Johander, & Kaakinen, 2019; Olkoniemi, Strömberg, & Kaakinen, 2019; Țurcan & Filik, 2016, 2017]. These studies generally find that comprehending irony incurs higher processing costs than comprehending literal language, suggesting that the salient meaning (i.e., the most familiar, frequent, and conventional meaning) is activated by default and must be overridden to interpret ironic statements, irrespective of how biasing the context is [Giora, 1997, 2003].…”
Section: Introductionmentioning
confidence: 99%